Ruído no parque nacional da Peneda-Gerês, Portugal - António P. O. Carvalho (2013)
This study characterizes the soundscape in the Peneda-Geres National Park (Portugal) using the parameters LAeq, LAFmin, LAFmax, LA10, LA50, and LA90, together with data collected at the site, such as the origin and duration of the noise traced. There were LAeq values between 33 and 51 dB and quieter areas were found in isolated locations and noisier near populated areas and water points. The acoustic situation of the studied area is compared with some U.S. national parks and with a large urban park in the city of Porto, Portugal.